2018
DOI: 10.1002/chir.23009
|View full text |Cite
|
Sign up to set email alerts
|

Pimarane diterpenes: Natural source, stereochemical configuration, and biological activity

Abstract: Plants and fungi are seemingly inexhaustible sources of interesting natural products with remarkable structural and biological diversity. One of the most important groups is the terpenes, ubiquitous natural products that are generated by 2 now well-established biosynthetic pathways: the older mevalonate and the more recently discovered 1-deoxyxylulose-5-phosphate. Among the diterpenes, the pimarane diterpenes are a very representative subgroup with several and interesting biological activities resulting from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(82 citation statements)
references
References 122 publications
(304 reference statements)
3
79
0
Order By: Relevance
“…To date, a number of potential diterpenoids and their synthetic derivatives have been recognized for their important biological activities. Numerous examples on diterpenoids can be found in the literature including cassane and norcassane diterpenes , rosemary diterpenes , phytol , and pimarane .…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of potential diterpenoids and their synthetic derivatives have been recognized for their important biological activities. Numerous examples on diterpenoids can be found in the literature including cassane and norcassane diterpenes , rosemary diterpenes , phytol , and pimarane .…”
Section: Discussionmentioning
confidence: 99%
“…They exhibited inhibitory activity against some marine phytoplankton species [99]. Pimarane diterpenes are a widely distributed class of terpenes that are produced by a wide variety of organisms, and marine-derived fungi are no exception [100]. In 2012, Sun et al reported the isolations of five new oxygenated pimarane diterpenes, named scopararanes C–G ( 286 – 290 ), from a marine sediment-derived fungus Eutypella scoparia FS26.…”
Section: Terpenoids Terpenes and Meroterpenoidsmentioning
confidence: 99%
“…Pimarane diterpenoids have been encountered as secondary metabolites of higher plants, fungi, and marine organisms. 1 This class of diterpenes can be derived from the original core by substitution, hydroxylation, acetylation, rearrangement, bromination, and ring expansion reactions. 2 Since the isolation of pimaric acid, the rst example of this class, in 1839, 3 pimarane diterpenoids have attracted considerable interest due to their remarkable structural diversity and great antimalarial, 4 antibacterial, 5 antifungal, 6 antiviral, 7,8 phytotoxic, 6 cytotoxic, [9][10][11][12] AChE-inhibitory, 13 and anti-inammatory activities.…”
Section: Introductionmentioning
confidence: 99%